Generation Y: indigenous tourism interests and environmental values. Issue 2 (3rd May 2016) - Vermeersch, Laura; Sanders, Dale; Willson, Greg
Abstract : Indigenous tourism is an important sector worldwide. While demand for Indigenous tourism has previously been examined, there is a paucity of research on the relationship between Generation Y's (Gen Y) Indigenous tourism interests and their environmental values. This paper reports the results of exploratory, qualitative semi-structured interviews with 14 Gen Y members in Western Australia. The Gen Y participants in this study displayed strong egocentric environmental values, and a disconnect between stated environmental ideals and travel behaviour. They were also largely disinterested in Australian domestic Indigenous tourism, showing a strong preference to engage with international Indigenous tourism that included cultural and social components rather than nature-based.